Early Lumen-Apposing Metal Stent Dysfunction Complicating Endoscopic Ultrasound-Guided Gastroenterostomy: A Report of Two Cases - Janine B. Kastelijn; Veronique Van der Voort; Alderina Bijlsma; Leon M. G. Moons; Matthijs P. Schwartz; Frank P. Vleggaar (Korean Society of Gastrointestinal Endoscopy, 2021)
Endoscopic ultrasonography-guided gastroenterostomy using a lumen-apposing metal stent has emerged as a novel technique in the palliative treatment of malignant gastric outlet obstruction. Endoscopic ultrasonography-guided gastroenterostomy seems to have the potential to provide long-lasting patency in a minimally invasive manner. Low reintervention rates have been described. We report two cases with early lumen-apposing metal stent dysfunction, compromising patency. One case showed food impaction after three weeks, and hyperplastic tissue overgrowth with a buried distal flange six weeks after stent placement. The latter was successfully treated by argon plasma coagulation, stent removal, and deployment of a larger-diameter lumen-apposing metal stent. The second case showed a narrowed luminal diameter of the stent and jejunal pressure ulcerations after three weeks. The narrowing was successfully treated by balloon dilation. Eight weeks later, hyperplastic tissue overgrowth at the distal flange of the stent and a gastro-colonic fistula were diagnosed, followed by extensive reconstructive surgery.